Enterprise Mashups: A New Approach for Business Solutions - Paredes-Valverde, Mario; Alor-Hernández, Gine (Lámpsakos (revista descontinuada), 2012)
A mashup is a Web application that integrates content from different providers in order to create a new service which is not offered by the content provider. The development of this kind of applications involves activities such as accessing heterogeneous sources, combining data from different data sources and building graphical interfaces. This factor limits non-experienced computer users to develop these applications. However, nowadays there are enterpriseoriented tools that allow non-experienced user for building mashups in order to respond business needs in an easy and rapid way. Due to this, the enterprise mashup approach has been widely adopted by a large number of enterprises. This paper presents an overview of the enterprise mashup approach, as well as a review of four enterprise-oriented tools which provide a set of features that allows non-expertise users developing mashups into an enterprise. Finally, we present the challenges to be addressed by enterprise-oriented mashup tools in order to provide an easier and faster way of developing mashups.